Composition of the European Parliament in the 2014-2019 term - Cegiełka, Katarzyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
Currently, representatives of 28 countries form the European Parliament. Their populations are characterized by a large disparity which leads to the need to seek methods of allocating the seats which are not based on proportional methods. They should have fulfilled the conditions of degressive proportionality by 2009. Although scientists have so far offered various solutions in line with the assumptions, MEPs did not take any of them. Furthermore, they changed the interpretation of the new rule in subsequent terms of office. At the same time, they have not determined a composition of the European Parliament which meets the conditions of degressive proportionality. In the paper, the author presents the degressive proportionality principle and analyzes the composition of the European Parliament in 2014-2019 term proposed by MEPs.
Didactics of Mathematics, 2012, Nr 9 (13), s. 25-34
Keywords: European Union; European Parliament; degressive proportionality; fair division; indivisible goods